Stress redistribution in rock mass surrounding underground excavations - Liau, Tai Wee. (2011)
Different factors that can affect the stress redistribution of an underground excavation work are examined and explored to find out how different factors from different aspect of an underground excavation can affect stress redistribution after excavation work is carried out.The software Phase2 developed by Rocsience is used in the analysis of existing data located from different sources to better understand how the different factors such as shapes of underground excavation, rock parameters surrounding excavated area, internal pressure of excavated area, in-situ stress before excavation and near-by excavation work can affect the stress redistribution after tunneling was carried out.